ARABIC AS A WINDOW IN PERCEIVING THE WORLD: A REVIEW OF SEMANTIC, EDUCATIONAL POLITICS AND LITERARY SOCIOLOGY - Luhuringbudi, Teguh; Liza, Fitri; Utami, Dewi Nita; Putra, Purnama (Journal of Arabic Language and Literature (ALLAIS), 2024)
This research paper aims to construct a theoretical-practical comprehension of Arabic as a means of perceiving the world. It is based on the content and principles of numerous previous dissertations. The paper's methodology employs qualitative and library research methods. During the analytical process, the theory of al-'Arabiyyah ka Nāfidhah 'alā al-Āyāt al-Kauniyyah (The Arabic language as a window on the cosmic verses), proposed by 'Alī 'Abd al-Mun'im al-Miṣriyy, is utilized. The three primary sources utilized include: 1) Semantik Bahasa Arab dalam Pandangan Al-Anbārī: Kajian Makna al-Taḍād di dalam Alquran by Mahyudin Ritonga (2013); 2) Politik Pendidikan Bahasa Arab di Perguruan Tinggi: Analisis Wacana atas Program Studi Bahasa Arab UIN Jakarta dan UI by Mauidlotun Nisa' (2018); and 3) Sastra dan Nasionalisme: Studi atas Puisi-puisi Mahjar 'Alī Aḥmad Bākathīr by Minatur Rokhim (2021). The study concludes that taking into account local and national environmental needs and interests can transform Arabic language knowledge into a capital asset for scientific, applied, and commercial purposes, thereby contributing to global unification.